2012
DOI: 10.1021/jp302763h
|View full text |Cite
|
Sign up to set email alerts
|

Chloroperoxidase-Catalyzed Epoxidation ofcis-β-Methylstyrene: Distal Pocket Flexibility Tunes Catalytic Reactivity

Abstract: Chloroperoxidase, the most versatile heme protein, has a hybrid active site pocket that shares structural features with peroxidases and cytochrome P450s. The simulation studies presented here show that the enzyme possesses a remarkable ability to efficiently utilize its hybrid structure, assuming structurally different peroxidase-like and P450-like distal pocket faces and thereby enhancing the inherent catalytic capability of the active center. We find that during epoxidation of cis-β-methylstyrene (CBMS), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 81 publications
4
33
0
Order By: Relevance
“…contribute -6.6 to -9.4 kJ/mol per residue to the formation of CPO-indole complex (see Table 2.4). This agrees with reports that these hydrophobic residues interact significantly with hydrophobic substrates such as cis-β-methylstyrene [107,108] and anthracene [176].…”
Section: Molecular Docking Models Of Indole Bound To Cposupporting
confidence: 92%
See 2 more Smart Citations
“…contribute -6.6 to -9.4 kJ/mol per residue to the formation of CPO-indole complex (see Table 2.4). This agrees with reports that these hydrophobic residues interact significantly with hydrophobic substrates such as cis-β-methylstyrene [107,108] and anthracene [176].…”
Section: Molecular Docking Models Of Indole Bound To Cposupporting
confidence: 92%
“…Although the use of computational method for the study of CPO is limited at status quo, this computational method is promising because of the rapid-growing computer technology. Recently, Morozov et al proposed that the simple steric considerations from the hydrophobic core (residues Phe 103, Ile 179, Val 182, and Phe 186) around the oxyferryl heme center govern the stereoselectivity of CPO [107,108], based on the molecular model of cis-β-methylstyrene, a substrate can be oxidized enantioselectively by CPO and H 2 O 2 .…”
Section: Computational Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest to our group is the epoxidation of olefinic substrates. The Chatfield research group has focused on the epoxidation of cis-β-methylstyrene (CBMS), 13,42 as CPO is capable of catalyzing this substrate to an enantiomeric excess of 96%, making CBMS an excellent substrate for determining the structural features responsible for enantioselectivity. 39 Additionally, CBMS has been used in prior experimental and computational studies.…”
Section: Epoxidationsmentioning
confidence: 99%
“…The imidazole side-chain nitrogens of His105 form hydrogen bonds with the carboxylate side chain of Glu183 and the backbone carbonyl oxygen of Asp106. This set of hydrogen bonds influences the effective pKa of the Glu183 carboxylate side chain, which participates directly in the formation of Cpd I. Additionally, His105 participates in a proton-shuttle during the acidbase catalysis of Cpd I. Molecular dynamics (MD) simulations 13 have shown that the distal pocket changes character from polar (peroxidase-like) to hydrophobic (P450-like)…”
mentioning
confidence: 99%